2020
DOI: 10.3390/ma13153333
|View full text |Cite
|
Sign up to set email alerts
|

Pseudo-Ductility, Morphology and Fractography Resulting from the Synergistic Effect of CaCO3 and Bentonite in HDPE Polymer Nano Composite

Abstract: Polymeric materials such as High density polyethylene(HDPE) are ductile in nature, having very low strength. In order to improve strength by non-treated rigid fillers, polymeric materials become extremely brittle. Therefore, this work focuses on achieving pseudo-ductility (high strength and ductility) by using a combination of rigid filler particles (CaCO3 and bentonite) instead of a single non-treated rigid filler particle. The results of all tensile-tested (D638 type i) samples signify that the microstructur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 40 publications
1
3
0
Order By: Relevance
“…Similar descriptions of CaCO 3 particles are given in the study of Minkowicz et al 17 CaCO 3 used together with the nano clay powder showed enhanced compatibility resulting in a high stress transfer from the matrix to the particles. The adequate dispersion can be confirmed from the details in our previous study 18 and also the details following herein.…”
Section: Resultssupporting
confidence: 79%
See 2 more Smart Citations
“…Similar descriptions of CaCO 3 particles are given in the study of Minkowicz et al 17 CaCO 3 used together with the nano clay powder showed enhanced compatibility resulting in a high stress transfer from the matrix to the particles. The adequate dispersion can be confirmed from the details in our previous study 18 and also the details following herein.…”
Section: Resultssupporting
confidence: 79%
“…We count the properties of (a) reorientation of clay in a sliding direction, (b) solid compatibilization, and (c) “dismantling” of clay layers as pivotal in polymer tribology for enhancing the wear properties of polymeric materials. Further, in the case of pseudo‐ductility, the clay layers reorient in the direction opposite to crack generation and crack propagation 18 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Elongation at break values of GS3 and JS were found to be 13.1% and 7.3%, respectively indicating more ductile nature of GS3 composite. 13 The observed tensile and flexural values of glass fabric-soy composites are, however, lower than those reported for glass fiber-soy oil-based epoxy composites 8 presumably due to poor fiber-to-fiber interaction, poor interatomic forces between soy resin to glass fabric, and low tensile yield of soy matrix. As GS3 showed highest tensile properties among other samples in the series, the composition used for development of the composite was considered as the optimum.…”
Section: Resultsmentioning
confidence: 78%